Teaching With Electronic Portfolios to Develop 21st Century Literacies (LEARNing Landscapes, 2013)
This article introduces an electronic portfolio, ePEARL, and how it has been used in classrooms to promote 21st century literacies. Using NCTE’s 21st Century Literacies framework, the authors provide examples of student work and classroom assignments to demonstrate how an electronic portfolio can support teachers integrating this framework and developing these skills in pedagogically meaningful ways.
Keywords: ePEARL; electronic portfolio; literacy; technology; teaching; 21st century